PENERAPAN HAK EKONOMI PENCIPTA TERHADAP KARYA MUSIK YANG DIGUNAKAN OLEH USAHA KEDAI KOPI UNTUK KEPENTINGAN KOMERSIAL DI DENPASAR - I Gede Mahatma Yogiswara; Asri Sarif; Gede Ari Darmawan I Nyoman Angga Setana Putra; I Nyoman Setana Putra; I Ketut Ferdy Tresnadiputra (Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2023)
The purpose of this scientific work is to find out and analyze the application of economic rights by the creators of musical works or songs to the use of music or songs by coffee shop business owners in Denpasar. This scientific work is empirical juridical law research. This thesis research uses library research techniques and interview techniques. This thesis research uses qualitative analysis techniques. The use of music or songs to support their business to attract consumers without permission will have a detrimental effect on the creator, as experienced by a Balinese songwriter named Agung Ocha, an indi musician, because his work is widely used by coffee shop entrepreneurs. There are factors that cause losses to creators from the use of music or songs by coffee shop business owners in Denpasar due to the fact that the copyrighted work is not registered with the LMKN and is not a member of the LMK so that the creator does not get royalties even though his work is played or commercialized by someone else. According to the procedure, in order to receive royalties, the work must be registered and become an LMK